2013
DOI: 10.1177/0959680113516405
|View full text |Cite
|
Sign up to set email alerts
|

A typology of trade union websites with evidence from Portugal and Britain

Abstract: Information and communication technologies can provide an important contribution to revitalizing trade unions, since the internet is faster, cheaper and more far-reaching than traditional communication methods. We propose a typology for analysing trade union websites, and apply this by comparing two national cases. The empirical research is limited to the websites of Portuguese and British civil service trade unions. We find that British unions take more advantage of the internet than those in Portugal; not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…In doing so, we chose to prioritise analysis of the website audience rather than simply examining its features, which has been the predominant approach of industrial relations scholars (see, e.g. Rego et al ., ).…”
Section: Background Data and Research Methodsmentioning
confidence: 97%
“…In doing so, we chose to prioritise analysis of the website audience rather than simply examining its features, which has been the predominant approach of industrial relations scholars (see, e.g. Rego et al ., ).…”
Section: Background Data and Research Methodsmentioning
confidence: 97%
“…Understanding how members experience new communication tools, therefore, requires knowledge of the union's internal and external context. Following Martinez Lucio (), other research by Martinez Lucio and Walker (), Panagiotopoulos () and Rego and Alves () has examined how the Internet, and more recently SM engagement, by and within unions varies substantially by country, and, as Panagiotopoulos () observes, potentially also by industry, organization and workplace context. Cockfield (), moreover, argues these technologies are not inevitably emancipatory and must be incorporated into a broader renewal strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Upchurch and Grassman (2016), in providing '"horizontalist" forms of distributing the means of expressing and framing the discourse (p. 643)', social networking sites have the potential to challenge traditional hierarchical power relations within unions. However, as Hodder and Houghton (2015) (2012) and Rego and Alves (2014) has examined how the Internet, and more recently SM engagement, by and within unions varies substantially by country, and, as Panagiotopoulos (2012) observes, potentially also by industry, organization and workplace context. Cockfield (2005), moreover, argues these technologies are not inevitably emancipatory and must be incorporated into a broader renewal strategy.…”
Section: Trade Union Communicationsmentioning
confidence: 99%
“…Researchers quickly saw the potential of the Internet for mobilization; they claimed that ICT would empower the union movement (Shostack 1999) and improve ordinary union work (Diamond and Freeman 2002), and suggested that the new technology could even be used to realize the labour movement's goal of internationalism (Lee 1997). One area of study focused on trade unions and Web 1.0 and investigated how unions use home pages and what type of information they post online Rego et al 2014). Existing studies on Web 2.0 have examined trade unions and social media, with a particular focus on the potential of social media for improving the interactions between a union and its members (Panagiotopoulos 2012), facilitating transnational networks (Dahlberg-Grundberg et al 2016) and building transnational labour solidarity .…”
mentioning
confidence: 99%